THE DYNAMICS OF ISLAMIC FAMILY LAW IN THE MODERN ERA: AN ANALYSIS OF TAGHAYYUR AL-FATWĀ AND AL-MUḤĀFAẒAH IN THE CHANGING MARRIAGE AGREEMENT PROVISIONS IN INDONESIA - Ulfazah, Yernati; Hafis, Muhammad; Elmiati, Nia; Zakariah, Asril Amirul (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2025)
Purpose: This study analyzes the application of the fiqhiyyah rules taghayyur al-fatwā and al-muḥāfaẓah in the context of changing marriage agreement provisions in Indonesia, specifically in the Regulation of the Minister of Religious Affairs Number 19 of 2018 (PMA 19/2018). The taghayyur fatwa rule refers to the flexibility of the fatwas, which can change according to the needs of society. Al-muḥāfaẓah emphasizes the importance of maintaining good old values while adopting new opinions that are more relevant and contextual. These two principles became the primary analytical framework for evaluating the dynamics of changes in marriage agreements in PMA 19/2018. These changes are inseparable from the challenges of the modern era, such as issues of gender equality, the protection of women's rights, and legal certainty in marriage. Methods: The research used a normative juridical method with a legislative approach. Data sources were obtained from libraries through legislation, books, and related articles. Findings- This study shows that the application of the rules of taghayyur fatwa and al-muḥāfaẓah in PMA 19/2018 reflects an effort of ijtihad to balance between maintaining the fundamental values of Islamic law (al-muḥāfaẓah) and accommodating the changes and dynamics of modern society (taghayyur fatwa). This change can be seen in the flexibility of the time needed to make a marriage contract, which could only be done before or during the marriage but can now be done during the marriage. Contribution/Limitations- PMA 19/2018 is a form of legal response to the development of modern society while ensuring that marriage law remains relevant, fair, and follows the principles of justice in Islam. Thus, PMA 19/2018 is proof of the adaptation of Islamic family law to contemporary challenges. The limitations of this study lie in its normative focus, without an empirical field analysis. Originality/Value- This research offers a family law perspective on the dynamics of modern society in dealing with contemporary issues, which can be a reference for academics and legal practitioners.